On the reaction mechanism of MnOx/SAPO-34 bifunctional catalysts for the conversion of syngas to light olefins. Issue 24 (2nd December 2021) - Coudercy, Christophe; L'hospital, Valentin; Checa, Ruben; Le Valant, Anthony; Afanasiev, Pavel; Loridant, Stéphane
Abstract : Methanol is a key reaction intermediate formed on MnO x that synergistically reacts with SAPO-34 to produce light olefins. Abstract : MnO x /SAPO-34 bifunctional catalysts are efficient for the conversion of syngas to light olefins. However, the reaction mechanism is still debated in particular the nature of the intermediate formed on MnO x (ketene vs. methanol). In this study, it was evidenced from catalytic data and in situ DRIFT measurements that methanol is a key reaction intermediate produced on MnO x that synergistically reacts with SAPO-34 to produce light olefins.